Praktek Pemberian Informasi Ketua RT tentang Pencegahan dan Penularan HIV/AIDS - Sri Widiyati; Budi Widiyanto; Adhani Windari (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The objective of study is to identify practice of informing community leaders on HIV/AIDS in sub Tanjungmas Semarang. This study used a descriptive analytic with cross sectional design. With a population sample of community leaders in this case the RT in the region of the village of Tanjung mas Semarang City with random sampling technique of 50 respondents. Used statistical test with chi-square. The result showed there is one variable that affects the results of statistical tests with significance level obtained p value 0.037, was means there is a relationship between attitudes to the practice of giving information about public figures in keluarahan Tanjungmas Semarang attitude intact affected by knowledge, beliefs and emotions. When the community leaders have heard about the causes, consequences/harm, prevention and transmission of HIV/AIDS and so on, then this knowledge will bring the community leaders to think of behavior towards prevention of HIV/AIDS on him and people they lead.